Pengembangan Perangkat Pembelajaran Berbasis Multiple Intelligences untuk Meningkatkan Motivasi dan Hasil Belajar Fisika Peserta Didik SMA - Siti Ismi Destari; Hairunnisyah Sahidu; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2022)
This research aims to develop a learning device based on the multiple intelligences that can be valid, practical, and effective to increase students' motivation and learning achievement in physics. In this research, the learning device was developed in form of a syllabus, teaching materials, lesson plans, student worksheets, and test instruments for learning achievement. This was a research and development (R&D) with a procedural development model, named the 4D model (define, design, develop, and disseminate). The average percentage of learning device validation related to syllabus, teaching materials, lesson plans, student worksheets, and test instruments of learning achievement was 86.00%, 83.00%, 81.00%, 80.05%, and 82.50%. The practicality of the learning device was able to be seen in the percentage of learning implementation in every meeting, it was 79.60% and 75.65%, while the students’ responses toward the learning process and the student worksheets got an average percentage of 80.91% and 77.68%. The effectiveness of learning devices was proved by the increase in students' cognitive learning achievement calculated by the N-Gain equation, the results were obtained 0.63 for the medium category. The average percentage of students' learning motivation also increased from 67.56% to 75.17%. Based on these results, the learning device that was developed is valid, practical, and effective to use with some revisions.